2016
DOI: 10.1007/s00405-016-3996-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the combination of platelet count and neutrophil–lymphocyte ratio in patients with hypopharyngeal squamous cell carcinoma

Abstract: Hypopharyngeal squamous cell carcinoma (HPSCC) is an aggressive disease with poor prognosis; but has no established biomarkers on the order of human papilloma virus and p16 in oropharyngeal carcinoma. This study investigated pre-treatment serum markers, including the combination of platelet count and neutrophil-lymphocyte ratio (COP-NLR) as a prognosis predictor in patients with HPSCC treated in our hospital. We retrospectively reviewed electronic medical records of 118 consecutive patients treated with curati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 23 publications
1
51
1
Order By: Relevance
“…This scoring system may better reflect the cancer’s anatomic and biologic status. Previous studies have found significant differences in conventional tumor-related factors and other inflammation-based markers among cancer patients categorized into different COP-NLR groups 1317. Additionally, a higher COP-NLR has consistently translated into poorer prognoses in a variety of cancers 1317.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This scoring system may better reflect the cancer’s anatomic and biologic status. Previous studies have found significant differences in conventional tumor-related factors and other inflammation-based markers among cancer patients categorized into different COP-NLR groups 1317. Additionally, a higher COP-NLR has consistently translated into poorer prognoses in a variety of cancers 1317.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found significant differences in conventional tumor-related factors and other inflammation-based markers among cancer patients categorized into different COP-NLR groups 1317. Additionally, a higher COP-NLR has consistently translated into poorer prognoses in a variety of cancers 1317. COP-NLR may be better applied to the estimation of cancer survival than other inflammation-based markers because it is cost efficient and reproducible, it is readily estimated prior to treatment, and it can be used to stratify cancer patients into different risk subgroups by scoring the two separate parameters 1317.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, PLR has been found to be an independent predictor of venous thromboembolism in cancer patients (Ferroni et al, 2015). COmbination of Platelet count and Neutrophil to Lymphocyte Ratio (COP-NLR) (Ishizuka et al, 2013, 2014; Feng et al, 2014a; Zhang H. et al, 2015; Nakahira et al, 2016) and Neutrophil-Platelet Score (NPS) (Watt et al, 2015) are predictors of survival for several types of cancer. Notably, some scoring systems that include evaluation of platelet count or function have higher predictive value in certain cancers than tools not analyzing platelets (Feng et al, 2014b; Ferroni et al, 2015; Sanchez-Salcedo et al, 2016), indicating that platelets may play a key role in cancer development and have prognostic value.…”
Section: Platelet Interaction With Immune Cells With Respect To Cancermentioning
confidence: 99%